PEMANFAATAN MINYAK BIJI KOPI (Fine Robusta Toyomerto) SEBAGAI BAHAN BAKU PEMBUATAN PARFUM EAU DE TOILETTE - Muhamad Nur Mustakim; Maya Sari; Muhammad Nur kholis (Agroindustrial Technology Journal, 2019)
Coffee bean oil is the result of extracting coffee beans that have aromatic compounds and can be used as fragrance for making perfumes. The purpose of this study was to make a perfume formula eau de toilette by mixing coffee bean oil. The results showed perfume with a mixture of 0.01 ml lemon formula, 2 ml coffee and 0.02 ml patchouli had longer fragrance resistance and organoleptic test results for overall fragrance and natural fragrance were preferred by panelists. The perfume formula which has the highest specific gravity and spot is owned by perfume with the addition of 1 ml of coffee. The difference in the addition of the amount of coffee bean oil in the perfume formulation gives a difference in the clarity of perfume.